Effect of breed on ovulation, induced by human chorionic gonadotropin, in cyclic mares - Buelbuel, Buelent; Soenmez, Mustafa (Natl Veterinary Research Inst, 2007)
The objective of this study was to compare the efficacy of human chorionic gonadotropin (hCG) for the stimulation of ovulation within 48 h after treatment in mares, which had a >= 35 mm follicle. A total of 41 oestrus cycles of 21 mares (9 Thoroughbred, 6 Dutch Warmblood, and 6 Friesian), between 7 and 12 years of age were used for this study. All the mares were intramuscularly treated with Hcg, at the dose of 3 000 IU when a follicle >= 35 mm was detected. They were examined daily by transrectal ultrasonography, until the ovulation was confirmed. It was found that the diameter of follicle before ovulation was more significant, and oestrus duration was longer in Friesian mares than those of Thoroughbred and Dutch Warmblood ones. Moreover, the percentage of mares ovulating within 48 h after hCG treatment was significantly lower in Friesian mares, when compared to that of the other breed mares. There was no significant difference in these parameters between Thoroughbred and Dutch Warmblood mares. In conclusion, the efficacy of hCG may be different among mares of different breeds. The percentage of ovulation within 48 h after hCG treatment was lower in Friesian mares when compared to the other breeds. Therefore, various strategies are needed for the stimulation of ovulation in Friesian mares.
Keywords: mare; human chorionic gonadotropin; breed; ovulation